Liderazgo y gestión administrativa en el desarrollo organizacional de la escuela Club Rotario. Diseño de un manual de procedimientos administrativos. - Karolys Tobar, Alexandra Elizabeth (2016)
In this research the aim was a manual of administrative procedures for the organicfunctional structure at Club Rotario School of Latacunga, in order to get an organizational development oriented managers, teachers, workers and parents. The theoretical part was based on the main management theories. It was about the administrative processes analyzing its phases to get an organizational development, prioritizing the leadership to get an appropriate climate that is a very important factor if you want to achieve a harmonious development to achieve the effectiveness, efficiency and effectiveness of the human element. The organization is the strategic point which acts between the planning and the execution. The objectives of the educative institution must be considered according to the mission, vision, policies and philosophy of the institution. The elements involved are humans, materials and technological are divided in the work, the definition of departments and their functions, the relationships between people, the definitions of functions, the selections of working methods and maintenance of the human environment . The theory and practice of this investigation was in the philosophical approach of the main theories of management that are related to variables: leadership and management and administrative organization because we believe that all the elements that are a great engine that is the organization, and that administrators should apply the conceptual, human and technical skills; because the technical skill is considered essential inside at lower levels of administration, human capacity is important too in all levels and the conceptual human capacity is increased according the activities that a person develops in an administrative system.